Studies on erythropoietin responses in cattle experimentally infected with trypanosoma congolense. - Buza, J.J. (University of Nairobi, 1992)
Since the anaemia of T. congolense infection, which has been shown to be mainly due to erythrocyte destruction by macrophages of the mononuclear phagocytic system, has been shown to be associated with poor reticulocyte response, a study was designed to verify if the unresponsiveness is attributable to low erythropoietin levels. In the absence of commercially available bovine erythropoietin, a radioimmunoassay based on human urinary erythropoietin was assessed in measuring bovine erythropoietin levels, but was found to be unsuitable, presumably because the polyclonal antibody to human erythropoietin could not recognise bovine erythropoietin. An in vitro bioassay which indirectly measures erythropoietin levels by utilising erythropoietin's stimulatory effect on 1251-deoxyuridine (IUDR) incorporation in DNA of spleen cells from phenylhydrazine treated mice was able to measure erythropoietin levels in bovine plasma. The assay could detect minimum of 62.5 mU/ml of erythropoietin in plasma. Using the in vitro bioassay, increased erythropoietin levels were detected in calves as early as 6 hours post-bleeding (hpb) of 50% of their estimated total blood volume. The peak levels of 1225 mU/ml was reached at 33hpb and dropped below the detection limit of the assay by 72hpb. Reticulocytes appeared in the blood of the calves by 72hpb and this was followed by a macrocytic hypochromic anaemia during the recovery period. From 18 day post-infection (dpi) onwards, undiluted plasma collected from T. congolense infected animals suppressed IUDR incorporation into spleen cells. Diluting the plasma five fold decreased its suppressive effect and allowed the detection of erythropoietin. (x) Using diluted plasma in the assay, distinct erythropoietin peaks were observed both in the acute stage of the disease when the packed cell volume (PCV) was dropping rapidly and in the chronic stage when the PCV had stabilised between 16-17%. Increased erythropoietic response occurred throughout the acute stage of the disease indicated by progressive increase in mean corpuscular volume. During the chronic stage of the disease (39-76 dpi) the anaemia was macrocytic hypochromic and there was very few reticulocytes (0.2-0.4%). From 76dpi, despite low PCV and peaks of elevated erythropoietin, the erythropoietic response waned as indicated by a normocytic normochromic anaemia and an absence of reticulocytes. This suggests the bone marrow was unresponsive to elevated plasma erythropoietin. Cattle treated in the chronic stage of T. congolense infections recovered their normal PCV although their erythropoietin levels were below the detection limit of the assay. The animal treated on 57dpi recovered its pre-infection PCV four weeks after treatment while an animal treated on 85dpi had only recovered 84% of its pre-infection PCV 11 weeks after treatment.